THE SENTINEL LYMPH NODE CONCEPT IN IA2–IIA2 STAGES CERVICAL CANCER: CLINICAL PERSPECTIVES - A. I. Berishvili; T. M. Kochoyan; N. V. Levkina; O. V. Li (Опухоли женской репродуктивной системы)
Cervical cancer is currently the second most common form of neoplasia worldwide and third in the female population. The standard surgical treatment, for stages IA2-IIA, is radical hysterectomy with pelvic lymphadenectomy. The risk of intraoperative (vessel or nerve damage) or postoperative complications (lymphedema) is high. The sentinel node concept can reduce risk of such complications but currently is not included in the standard treatment.